Development of Motion Graphic Animation Based on Microlearning Through Tiktok Application on Class Vi Globalization Material - Subiyanto, Fadhil Ilham; Soepriyanto, Yerry; Abidin, Zainul (Proceedings Series of Educational Studies, 2024)
The purpose of this study was to develop a microlearning-based motion graphic animation through the TikTok application on globalization material that is suitable for use and can improve the cognitive learning outcomes of grade VI students at SDN 1 Babadan. This development uses the Sadiman model which consists of 9 stages, namely needs analysis, formulation of learning objectives, formulation of materials, formulation of success measurement tools, writing media scripts, media production, validation, revision, ready-to-use media. The development results received a positive response from the validity test by material experts of 95.2%, while by media experts it was 89.6%. Then a field trial was conducted on grade VI students of SDN 1 Babadan with a result of 91% and a learning outcome test was carried out, namely a g value of 0.54 was obtained. Thus, it can be concluded that the development of microlearning-based motion graphic animation through the TikTok application on the Globalization material for grade VI is proven to be valid or suitable for use in learning, and can improve the learning outcomes of grade VI students on the Globalization material. Keywords: Motion Graphic Animation; Microlearning; Tiktok Application; Globalization